2020
DOI: 10.33448/rsd-v9i9.7524
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo de cordeiros suplementados com níveis de glicerol em substituição ao milho

Abstract: Objetivou-se com o experimento estudar os intervalos de tempo e o número de dias de observação para avaliação do comportamento ingestivo de cordeiros confinados. Utilizaram-se 25 animais castrados, com peso médio de 23,80 ± 2,0 kg. Os animais foram alojados em baias individuais e distribuídos ao acaso em cinco dietas, constituídas de volumoso (feno de capim tifton) e concentrados a base de milho, soja e níveis de glicerol, fornecidos na proporção de 60:40 (volumoso: concentrado), duas vezes por dia. O registro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In animal nutrition, studies have shown the benefits of glycerol in the diets of production animals [ 12 ]. When evaluating the ingestive behavior of sheep supplemented with increasing levels of glycerol, it was observed that the inclusion of up to 12% would not significantly interfere with nutrient intake, feed efficiency, or even dry matter and ingested fiber rumination.…”
Section: Introductionmentioning
confidence: 99%
“…In animal nutrition, studies have shown the benefits of glycerol in the diets of production animals [ 12 ]. When evaluating the ingestive behavior of sheep supplemented with increasing levels of glycerol, it was observed that the inclusion of up to 12% would not significantly interfere with nutrient intake, feed efficiency, or even dry matter and ingested fiber rumination.…”
Section: Introductionmentioning
confidence: 99%